The Correlation of Education, Employment, Parental Income and Social Emotional Development with the Nutritional Status of Preschool Children Living in Flood Areas - Penyami, Yuniske; Inayah, Maslahatul; Hartono, Mardi; Firdaus, Salsabela Nurul (Jurnal Keperawatan, 2024)
Nutrition is a biological factor that influences children's growth and development. In 2022, the World Health Organization stated that around 148.1 million children under five years old have a height that is not appropriate for their age or stunting, 45 million children are too thin compared to their height or wasting, and 37 million children are too heavy for their height or overweight..This study aims to determine the nutritional status of preschool children in flood areas and looking at the correlation of education, employment, parental income and children's social emotional development with the nutritional status of preschool children. The sample in this study was 114 preschool children aged 3 - 6 years who lived in flood areas. Sampling technique with cluster sampling. There are 9.6% of children who are very underweight, 29.8% are underweight, 15.8% are at risk of being overweight according to weight per age. According to height per age, there are 22% of children who are malnourished and 0.9% obese. According to BMI, there are 22.8% malnutrition and 18.4% malnutrition. There were 13.2% of children in the short category and 4.4% of very short children. There is a social emotional relationship between children and nutritional status according to BMIA. However, stunting and undernutrition or underweight are important findings in this study. These findings relevant for nursing to design and implement treatment or prevention interventions in overcoming nutritional problems in children. Future studies require surveys with larger samples and with more varied characteristics.